Spiritual health in an Spiritual-growing social context from Nahj al-Balagha perspective - Mahdi Fani; Mostafa Esmaeili; Morteza Abdoljabbari; Foroozan Atashzadeh-Shoorideh; Marzieh Karamkhani (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here Background and Objectives: Spiritual health is a dimension of human health which can grow in various contexts. These factors can be extracted from Islamic texts particularly from Nahj al-Balagha. Social factor is one of the growing factors in spiritual health. This study aimed to investigate spiritual-growing social factors from Nahj al-Balagha perspective. Materials and Methods: This content analysis study is based on personal and social teachings of Nahj al-Balagha through focusing on spiritual-growing social factors. In this study, Islamic documents and texts including Nahj al-Balagha Islamic sciences software were examined. Moreover, 500 articles were reviewed in the country's publication websites using "Nahj al-Balagha" keywords. From the corpus of the study, 97 articles were replication and the rest were related to various social, moral, literary, educational text-types. Among the reviewed articles, the subject of four articles was health and four articles were related to spiritual issues to some extent. Only one article was about the spiritual health in Nahj al-Balagha which was used in this study. Results: In this study, it was found that the rule of religious and society's leadership has an influential role in directing people towards moral and ethical values. In addition, the fight against poverty, the society's relative welfare, deterring discrimination and social inequality, and executing justice, will lead the society to moral values. Conclusion: According to what was said, it can be concluded that as spirituality has individual aspect, it can have social aspect too. In other words, it is possible to talk about spiritual society and materialistic and unspiritual society as well. Religious behaviors are crucial for the development of spirituality. Accordingly, the spiritual society is established when religious behaviors are pervasive in our society. Keywords: Nahj al-Balagha, Spirituality, Social factors For downloading the full-text of this article please click here